2021
DOI: 10.1017/jfm.2021.311
|View full text |Cite
|
Sign up to set email alerts
|

Flat plate drag reduction using plasma-generated streamwise vortices

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 82 publications
4
8
0
Order By: Relevance
“…The data of both uncontrolled and controlled boundary layers fit the law of the wall, i.e. u * =y * , for y * in the range 3.8-5, which is similar to the results of Cheng et al [11].…”
Section: Single-point Measurement Of Local Drag Reductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The data of both uncontrolled and controlled boundary layers fit the law of the wall, i.e. u * =y * , for y * in the range 3.8-5, which is similar to the results of Cheng et al [11].…”
Section: Single-point Measurement Of Local Drag Reductionsupporting
confidence: 87%
“…The dielectric barrier discharge (DBD) plasma flow control method [3][4][5][6], as an active flow control technology, has recently attracted a great deal of interest because of its advantages, e.g. no moving mechanical parts, a simple structure and a rapid response [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the plasma discharge the charged particles are subjected to the electric field generated by the asymmetric electrodes and collide with the neutral particles for momentum transfer, forming a directional jet from the exposed electrode to the buried electrode along the actuator surface. [4] DBD has many applications in active flow control, mainly lift increase and drag reduction, [5][6][7][8][9] noise reduction, [10,11] lateral force control [12,13] and suppression of flow separation. [14][15][16][17][18] The cited studies have demonstrated the flow control performance of DBD actuators.…”
Section: Introductionmentioning
confidence: 99%
“…The flow field characteristics of a drag plate located behind the cockpit on the back of the fuselage are simulated, and the effects of the width and deflection angle of the air brake on the pitching moment are studied (Cui et al ., 2018; Jafari et al ., 2018). The upper deflection of the spoiler and the upper deflection of the hinge flaps can produce greater rolling torque and avoid unnecessary increase of resistance (Wang et al ., 2017; Cheng et al ., 2021). An automatic triangle mesh generation method based on bubbles is presented (Wang et al ., 2019a, b).…”
Section: Introductionmentioning
confidence: 99%